2013
DOI: 10.1016/j.cgh.2013.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Markers of Inflammation in Patients With Ulcerative Colitis in Clinical Remission

Abstract: Background & Aims Mucosal healing, based on histologic analysis, is an endpoint of maintenance therapy for patients with ulcerative colitis (UC). There are few data on how histologic signs of inflammation correlate with endoscopic and peripheral blood measures of inflammation in these patients. We investigated patterns of histologic features of inflammation in patients with UC in clinical remission, and correlated these with endoscopic and biochemical measures of inflammation. Methods We performed a prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 25 publications
5
79
1
Order By: Relevance
“…Here we have shown that levels of ␣-1-microglobulin are increased in remission compared with control for UC patients and higher in these patients than in UC active disease. Sufferers in clinical remission are known to display the histological features of inflammation which correlate with endoscopic appearance (59). This AMBP cleavage product detectable in blood is able to highlight clinical remission and could therefore provide an alternative measure over colonoscopic evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Here we have shown that levels of ␣-1-microglobulin are increased in remission compared with control for UC patients and higher in these patients than in UC active disease. Sufferers in clinical remission are known to display the histological features of inflammation which correlate with endoscopic appearance (59). This AMBP cleavage product detectable in blood is able to highlight clinical remission and could therefore provide an alternative measure over colonoscopic evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Even though CRP short half-life of 19 h could not support such explanation, a recent study showed that a mean CRP levels of 5.4 mg/L (normal range) was associated with high histological inflammation scores in patients with ulcerative colitis during clinical remission. 45 Such results raise awareness to the fact that patients in clinical remission from UC still may have inflammation.…”
Section: Discussionmentioning
confidence: 96%
“…It represents the most metabolically active compartment of the body and catabolic conditions may lead to its reduction. 17 It is plausible that more extensive UC is associated with less protein deposits, as seen in other diseases, 45 and/ or related with high catabolic conditions. 17 Considering the results found in our population we might suggest that patients with better lean body mass had a lower susceptibility to the development of more extensive injury.…”
Section: Discussionmentioning
confidence: 99%
“…Histological inflammation is common even when the mucosa appears normal [18]. Accumulated evidence indicates that persistent histological disease is associated with an increased risk of hospitalization, colectomy, relapse, and colorectal neoplasia [19][20][21].…”
Section: Histological Mucosal Healingmentioning
confidence: 99%